TEKNIK MIND MAPPING DALAM PEMBELAJARAN MEMBACA (DOKKAI) BAHASA JEPANG TINGKAT DASAR - Yuki Arif Gumilar, - (2021)
This research is motivated by several problems that arise in the Japanese language learning process. One of the problems is the ability to understand Japanese texts. This study discusses the Mind Mapping technique in the Japanese Reading (Dokkai) learning. In the reality of learning, this reading skill is often neglected. In this study, a Mind Mapping research will be presented which is focused on the ability to read Japanese texts. The purpose of this research is to improve reading skills to understand students' reading, which is a challenge that must be faced by teachers; describe the quality of the results of the development of Mind Mapping techniques in learning to read Japanese texts and describe the effectiveness of using Mind Mapping techniques in learning to read Japanese texts (Dokkai). The type of research used is quantitative research. This study involved Japanese language learners in Daihatsu Batch 4. Data on the validity of the normality test, homogeneity test and hypothesis testing were obtained using pre-test and post-test as well as the distribution of the questionnaire. The data obtained were analyzed quantitatively. From the calculation results, there are significant differences in learners between the experimental class and the control class, before and after the application of the Mind Mapping technique. Based on the results of the questionnaire, Mind Mapping is one of the varied, innovative and effective techniques. Mind Mapping Technique is good to be applied in learning to read Japanese texts. KEYWORDS : Mind map, dokkai, Japanese